An analysis of levels and factors of teacher-librarian collaboration in selected public science high schools in Metro Manila - Trinidad, Jerome V. (School of Library and Information Studies, University of the Philippines Diliman, 2013)
School libraries exist to support the education the school brings. In the 21st century, our school librarians are changing roles in order to add more in this support. In all their new roles as information specialist, teacher, instructional partner and program administrator (AASL & AECT, 1998), they have to involve themselves in a healthy collaboration with teachers.